Value-based learning of Tri Kaya Parisudha for the interpersonal skills of students in early childhood education schools - Hartawan, I Made; Sumadi, Tjipto; Nurani, Yuliani (Edelweiss Applied Science and Technology, 2025)
The low level of interpersonal intelligence has implications for disrupted social and pedagogical activities, such as the emergence of problems with students who like to disturb their classmates. This reality was found in Early Childhood Education Institutions in Buleleng Regency, Bali. Therefore, a local value conception is needed for this issue. This research presents the urgency of Tri Kaya Parisudha as a learning paradigm while also focusing on answering two formulated problem statements, namely: a) why is Tri Kaya Parisudha-based learning important to implement as a medium for developing the interpersonal skills of early childhood?; b) how can Tri Kaya Parisudha-based learning develop the interpersonal skills of early childhood? The purpose of this research is to explain the approach of value-based learning using Tri Kaya Parisudha as a medium to produce learning and enhance children's interpersonal skills in interacting within the school environment, both with peers and teachers. The method used is qualitative, emphasizing findings based on observation and interview activities in several schools in Buleleng Regency. Observations and interviews were conducted at Sinar Harapan Kaliasem School, Kasih Ibu School, Panca Dharma Seririt School, and Sathya Sai Kumara Singaraja. The application of these two aspects is used to examine the learning of each school, whether they implement the values of Tri Kaya Parisudha or not. The background of Tri Kaya Parisudha (manacika, wacika, and kayika) creates the construction of interpersonal character in early childhood through cognitive, affective, and psychomotor aspects. With the application of these local values, students' interpersonal skills become applicable because they build social sensitivity (social sensitivity, produced from the internalization of manacika and kayika values), social insight (social insight produced from the implementation of manacika and kayika values), and social communication (social communication produced from the implementation of manacika, kayika, and wacika). Tri Kaya Parisudha becomes a local value that can be synchronized with pedagogical aspects because it creates students' interpersonal skills.